A study of relationships among technical, tactical, physical parameters and final outcomes in elite soccer matches as analyzed by a semiautomatic video tracking system - Filetti, C.; Ruscello, B.; D`Ottavio, S.; Fanelli, V. (Perceptual and Motor Skills, 2017)
The performance of a soccer team depends on many factors such as decision-making, cognitive and physical skills, and dynamic ever-changing space-time interactions between teammate and opponents in relation to the ball. Seventy (n = 70) matches of the Italian SERIE A season 2013-2014 were investigated to analyze the mean performance of 360 players in terms of physical (physical efficiency index; PEI) and technical-tactical (technical efficiency index; TEI) standpoints. Using a semiautomatic video analysis system that has incorporated new parameters able to measure technical-tactical and physical efficiency (Patent IB2010/002593, 2011-ISA), the correlation between these new variables and how much it relates to the likelihood of winning were verified. Correlations between TEI and PEI were significant (n = 140, r = .60, p < .001), and TEI showed a higher likelihood of winning than PEI factors (p < .0001 vs. .0001, CI 95% [1.64, 3.00] vs. [1.28, 2.07]). Higher TEI and TEI + PEI differences between the teams were associated with a greater likelihood of winning, but PEI differences were not. Key performance indicators and this performance assessment method might be useful to better understand what determines winning and to assist the overall training process and match management.